2016
DOI: 10.1093/elt/ccw047
|View full text |Cite
|
Sign up to set email alerts
|

Investigating teacher perceptions of feedback

Abstract: Investigating teacher perceptions of feedback

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
2
15
0
3
Order By: Relevance
“…(…) Teachers who operate without awareness of their students' points of view often doom students to dull, irrelevant experiences, and even failure. Interestingly, this move from behaviouristic towards humanistic and constructivist approaches has not been fully reflected in research -although there is a relatively large body of studies on teachers' perceptions of and beliefs about different facets of teaching (Lee, Leong & Song, 2016;Pajares, 1992) and assessment (e.g. Leung, 2004;Sahinkarakas, 2012), our understanding of learners' perceptions of the foreign language (FL) learning and teaching, particularly in terms of assessment, is limited.…”
Section: Notementioning
confidence: 99%
“…(…) Teachers who operate without awareness of their students' points of view often doom students to dull, irrelevant experiences, and even failure. Interestingly, this move from behaviouristic towards humanistic and constructivist approaches has not been fully reflected in research -although there is a relatively large body of studies on teachers' perceptions of and beliefs about different facets of teaching (Lee, Leong & Song, 2016;Pajares, 1992) and assessment (e.g. Leung, 2004;Sahinkarakas, 2012), our understanding of learners' perceptions of the foreign language (FL) learning and teaching, particularly in terms of assessment, is limited.…”
Section: Notementioning
confidence: 99%
“…Some studies have highlighted the impact of contextual constraints like limited time, exam pressure and instructional requirements in teacher practices of providing feedback (e.g. Lee 2009;Lee, Leong and Song 2017). Besides, research has also shown that classroom experiences play a role in constructing language teachers' beliefs, and guide their selection and adjustment of teaching strategies for coping with everyday instructional challenges (Borg 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another reason that motivates this study is to investigate the effectiveness of oral feedback to assist and improve students' English language proficiency. Regarding this matter, several studies have been found that investigates students' language improvement using feedback (Kahraman & Yalvac, 2015;Lee & Song, 2016;Elwood & Bode, 2014;Baz, 2016). However, most of the studies are focusing on written feedback instead of oral feedback.…”
Section: Introductionmentioning
confidence: 99%